2012
DOI: 10.1186/1743-422x-9-98
|View full text |Cite
|
Sign up to set email alerts
|

Anti-herpes virus activities of bioactive fraction and isolated pure constituent of Mallotus peltatus: an ethnomedicine from Andaman Islands

Abstract: BackgroundViral infections, particularly the infections caused by herpes simplex virus (HSV), represent one of the most serious public health concerns globally because of their devastating impact. The aim of this study was to evaluate the antiviral potential of methanolic crude extract of an ethnomedicine Mallotus peltatus, its active fraction and pure compound, against HSV-1 F and HSV-2 G.ResultThe cytotoxicity (CC50, the concentration of 50% cellular toxicity), antiviral effective concentration (EC50, the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 44 publications
0
50
0
Order By: Relevance
“…This may indicate that the extract probably interferes with post-absorption and early stages of HSV-1 replication. Similarly, it has been reported that the crude methanol extract of Mallotus peltatus leaves and Cuminum cyminum L seeds inhibited HSV-1 replication in the early stage and adsorption, respectively [21,22]. These results, together, might indicate that some herbal extracts are able to interact with this virus in the intracellular stages of replication.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…This may indicate that the extract probably interferes with post-absorption and early stages of HSV-1 replication. Similarly, it has been reported that the crude methanol extract of Mallotus peltatus leaves and Cuminum cyminum L seeds inhibited HSV-1 replication in the early stage and adsorption, respectively [21,22]. These results, together, might indicate that some herbal extracts are able to interact with this virus in the intracellular stages of replication.…”
Section: Discussionmentioning
confidence: 51%
“…This experiment, in which HSV-1 infected cells were treated with different doses of the extract at 1 h before and 24 h after the infection, was carried out according to previously described procedures with minor modifications [21]. In brief, approximately, 5 × 10 5 Vero cells/well were seeded onto 96-well plates with final volume of 100 µL per well and cultured for 24 h at 37 °C.…”
Section: Time-course Anti-virus Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The cell monolayer sheet was stained with 0.1% crystal violet staining solution for at least 15 min, then removed by aspiration and rinsing with distilled water, then the absorbance was measured with microplate reader (Bio-Rad 550) at wavelength of 490 nm. The viral inhibition rate was calculated according to the study of Bag et al (2012) and Dargan (1998) as follows:…”
Section: Evaluation Of Cytotoxicity Of Olive Leaves Crude Extract Fomentioning
confidence: 99%